Employee Motivation and Commitment Among Senior High School Teachers in Urdaneta City National High School - Samera, Norman (SAFE-Network, 2025)
The purpose of this study is to look into the level of organizational motivation and commitment, as well as the relationship between motivation and organizational commitment, in the Urdaneta City National High School. The relationships between organizational motivation and commitment were investigated using different methodologies and statistical tools. A total of 22 respondents participated in the research survey. A questionnaire was used to collect data for this study. The